Investigations on power consumption, pelleting temperature, pellet quality, and sugar yield in pelleting of cellulosic biomass - Zhang, Qi (Kansas State University, 2013)
The U.S. economy has been depending on petroleum-based liquid transportation fuels (such as gasoline, diesel, and jet fuels). Currently, about 50% of petroleum used in the U.S. is imported. Petroleum is a finite and non-renewable energy source and its use emits greenhouse gases. Therefore, it is extremely important to develop domestic sustainable alternatives for petroleum-based liquid transportation fuels. Ethanol produced from cellulosic biomass can be such an alternative. However, several technical barriers have hindered large-scale, cost-effective manufacturing of cellulosic ethanol. One such barrier is related to the low density of cellulosic feedstocks, causing high cost in their transportation and storage. Another barrier is low efficiency in conversion of cellulose to fermentable sugar (pretreatment and enzymatic hydrolysis are two major conversion processes), causing high cost in pretreatment and enzymatic hydrolysis of cellulosic biomass. Ultrasonic vibration-assisted (UV-A) pelleting increases both density and sugar yield of cellulosic feedstocks. Incorporating UV-A pelleting into cellulosic ethanol manufacturing may help realize cost-effective manufacturing of cellulosic ethanol. This PhD dissertation consists of 13 chapters. An introduction is given in Chapter 1. Chapter 2 presents a literature review on related topics. Experimental studies regarding effects of input parameters (such as particle size, pressure, and ultrasonic power) on output parameters (density, durability, stability, and sugar yield) are presented in Chapters 3–4. In Chapters 5–6, comparisons are made between UV-A pelleting and ring-die pelleting (a traditional pelleting method) in terms of pellet properties (density and durability), power consumption, and sugar yield under different conditions. Next, effects of input parameters (such as biomass type, particle size, moisture content, pelleting pressure, and ultrasonic power) on power consumption are studied in Chapters 7–9. Chapter 10 presents an investigation on biomass temperature in UV-A pelleting. Chapter 11 presents an investigation on effects of UV-A pelleting on sugar yield and chemical composition of cellulosic biomass. Chapter 12 presents an investigation on influence of UV-A pelleting on biomass characteristics (such as crystallinity index, thermal properties, and morphological structure). Finally, conclusions are presented in Chapter 13.
Keywords: Power consumption; Pelleting temperature; Pellet qaulity; Sugar yield; Agriculture, General (0473); Biochemistry (0487); Industrial Engineering (0546)